2013 IEEE 3rd Portuguese Meeting in Bioengineering (ENBENG) 2013
DOI: 10.1109/enbeng.2013.6518420
|View full text |Cite
|
Sign up to set email alerts
|

Computational model of the LGMD neuron for automatic collision detection

Abstract: In many animal species it is essential to recognize approach predators from complex, dynamic visual scenes and timely initiate escape behavior. Such sophisticated behaviours are often achieved with low neuronal complexity, such as in locusts, suggesting that emulating these biological models in artificial systems would enable the generation of similar complex behaviours with low computational overhead. On the other hand, artificial collision detection is a complex task that requires both real time data acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…The experimental data is adapted from [101]. model encoding onset and offset responses by luminance increments and decrements, adapted from [114], (b) a modified LGMD1 model for multiple looming objects detection, adapted from [233], (c) a simplified LGMD1 model for collision avoidance of an UAV, adapted from [188], (d) a modified LGMD1 model with enhancement of collision selectivity, adapted from [133,132], (e) a modified LGMD1 model with a new layer for noise reduction and spikingthreshold mediation, adapted from [198,197], (f) an LGMD1 neural network based on the modelling of elementary motion detectors for collision detection in ground vehicle scenarios, adapted from [91]. Based on this LGMD1 modelling theory, a good number of models have been produced during the past two decades; these works have not only been extending and consolidating the LGMD1's original functionality for looming perception, but also investigating the possible applications to mobile machines like robots and vehicles.…”
Section: Computational Models and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental data is adapted from [101]. model encoding onset and offset responses by luminance increments and decrements, adapted from [114], (b) a modified LGMD1 model for multiple looming objects detection, adapted from [233], (c) a simplified LGMD1 model for collision avoidance of an UAV, adapted from [188], (d) a modified LGMD1 model with enhancement of collision selectivity, adapted from [133,132], (e) a modified LGMD1 model with a new layer for noise reduction and spikingthreshold mediation, adapted from [198,197], (f) an LGMD1 neural network based on the modelling of elementary motion detectors for collision detection in ground vehicle scenarios, adapted from [91]. Based on this LGMD1 modelling theory, a good number of models have been produced during the past two decades; these works have not only been extending and consolidating the LGMD1's original functionality for looming perception, but also investigating the possible applications to mobile machines like robots and vehicles.…”
Section: Computational Models and Applicationsmentioning
confidence: 99%
“…10. These computational models consist of new methods to enhance the collision selectivity to approaching objects [133], new layers to reduce environmental noise [198,197], and etc.There are also researches on corresponding applications for cars [124,91] and mobile robots [43], as well as implementations in hardware like field-programmable gate array (FPGA) [132].…”
Section: Computational Models and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To realize the neural characteristics of LGMDs, a few computational models have been proposed for LGMD1 [1], [19], [20], [23], [30] and successfully utilized in vision-based platforms such as vehicles [14], [15] and robots [3], [16]- [18], [24], [31] for collision detection. Nevertheless, very little modeling works have been conducted for LGMD2.…”
Section: A Lgmds Neural Characteristics and Modelsmentioning
confidence: 99%
“…Such a fascinating neuron has been computationally modelled as collision selective visual neural networks or models (e.g. [2,11,17,19]), and applied in mobile machines like ground robots [5,7,10] and UAVs [15], and also embodied in hardware implementations like the FPGA [12]. These works have partially reproduced the LGMD's responses and demonstrated that it features efficient neural computation for quick and reliable looming or collision sensing.…”
Section: Introductionmentioning
confidence: 99%